Gas venting behavior and early detection performance in energy storage system battery modules under various thermal runaway scenarios - Jong Eun Kim; Hong Sun Ryou; Young Man Lee; Seong Hyuk Lee (Case Studies in Thermal Engineering)
The present study aims to numerically examine the gas venting behavior and early detection performance in energy storage system (ESS) modules under various thermal runaway scenarios. Extensive CFD simulations for a pouch-type battery are conducted using the commercial code ANSYS FLUENT 2020 R2 to estimate the detection times in ESS battery modules with multiple cells for different venting positions and directions within the module. This study also investigates the influence of cooling fan intensity on gas propagation and detection time. The results show that detection time decreases when venting in the battery cells occurs closer to the outlet, and the left-side venting is detected faster than the right-side venting. Moreover, increasing the fan intensity by 30 % enables detection within 1.0 s, even in battery cells that are furthest from the gas detector. When venting occurs in the last cell, the detection time difference between the left-side and right-side venting increases as the cooling fan intensity increases.